Degrasyn exhibits antibiotic activity against multi-resistant Staphylococcus aureus by modifying several essential cysteines. Issue 19 (10th February 2020) - Lee, Kyu Myung; Le, Philipp; Sieber, Stephan A.; Hacker, Stephan M.
Abstract : Degrasyn was found to exhibit antibiotic activity against multi-resistant Staphylococcus aureus . Chemical proteomics revealed insights into its mode of action. Abstract : Degrasyn inhibits deubiquitination enzymes and has anti-cancer activity. We here show that it also exhibits antimicrobial activity against multi-resistant Staphylococcus aureus . Structure activity relationship studies demonstrate an important role of the electrophilic α-cyanoacrylamide moiety as a Michael acceptor. A suite of chemical proteomic techniques unraveled binding of this moiety to various cysteine residues of essential proteins in a reversibly covalent manner.